Postural Control in Bilateral Vestibular Failure: Its Relation to Visual, Proprioceptive, Vestibular, and Cognitive Input - Sprenger, Andreas; Wojak, Jann F.; Jandl, Nico M.; Helmchen, Christoph (Frontiers in Neurology, 2017)
Patients with bilateral vestibular failure (BVF) suffer from postural and gait unsteadiness with an increased risk of falls. The aim of this study was to elucidate the differential role of otolith, semicircular canal, visual, proprioceptive and cognitive influences on the postural stability of BVF patients. Center of pressure displacements were recorded by posturography under six conditions: target visibility; tonic head positions in the pitch plane; horizontal head shaking; sensory deprivation; dual task and tandem stance. Between-group analysis revealed larger postural sway in BVF patients on eye closure but with the eyes open, BVF did not differ from healthy controls. Head tilts and horizontal head shaking increased sway but did not differ between groups. In the dual task condition, BVF patients maintained posture indistinguishable from controls. On foam and tandem stance, postural sway was larger in BVF, even with the eyes open. The best predictor for the severity of bilateral vestibulopathy was standing on foam with eyes closed. Postural control of our BVF was indistinguishable from healthy controls once visual and proprioceptive feedback is provided. This distinguishes them from patients with vestibulo-cerebellar disorders or functional dizziness. It also explains that postural unsteadiness of BVF patients can be missed easily if not examined by conditions of visual and/or proprioceptive deprivation. In fact, the best predictor for vestibular hypofunction (VOR gain) was examining patients standing on foam with the eyes closed. Postural sway in that condition increased with the severity of vestibular impairment but not with disease duration. In the absence of visual control, impaired otolith input destabilizes BVF with head retroflexion. Surprisingly, stimulating deficient semicircular canal does not distinguish patients from controls possibly reflecting a shift of intersensory weighing towards proprioceptive-guided postural control. Accordingly, proprioceptive deprivation heavily destabilizes BVF, even when visual control is provided. BVF should be tested with eye closure while standing on foam or tandem stance.